Action civics education and civic outcomes for urban youth: An evaluation of the impact of Generation Citizen. Issue 3 (1st October 2018) - Cohen, Alison K.; Littenberg-Tobias, Joshua; Ridley-Kerr, Abby; Pope, Alexander; Stolte, Laurel C.; Wong, Kenneth K.
In action civics education, an emerging promising practice, students learn civics through taking action on a community issue of interest. We examine the action civics programme Generation Citizen (GC) using quantitative and qualitative student survey data. Our quantitative analyses used a quasi-experimental study design and a multilevel model. Participation in GC was associated with increased action civics knowledge, and there were some variations in impact by programme and classroom characteristics. We also qualitatively analysed students' short reflections upon programme completion and found that students feel more prepared for civic action. Action civics shows promise for improving student civic outcomes, but more research, including longitudinal follow-up, is needed. Given the variations in impact that we observed, action civics practitioners should carefully choose the implementation setting.